THE EFFECT OF MARKETING PUBLIC RELATIONS STRATEGY ON THE IMAGE OF SCIENTIA SQUARE PARK THEMATIC THEME PARK - Gerut Gumay, M. Putra; Andrini, Susi (Transpublika Publisher, 2024)
Technological advances in the era of digitization make Public Relations practitioners strive to be able to utilize the media in making strategies. Technological advances have created new forms of interacting and socializing, one of which is the innovation of communication technology in the form of social media. Local attractions Scientia Square Park tourism in South Tangerang amusement park carries the concept of a thematic amusement park with special characters that pay attention to aspects of accuracy, comfort, safety, beauty, convenience, greenery and maintenance. Scientia Square Park utilizes Instagram as one the marketing strategies for thematic Amusement Park Public Relations (Scientia Square Park). This study aims to determine whether there is an influence of Marketing Strategy Public Relations to the image of the thematic amusement park (Scientia Square Park) on Instagram account @Scientiasquare.park. This research uses the theory of Public Relations Marketing strategies, namely Push, Pull, Pass Strategy from Samuel L Harris and image according to Frank Jefkins in Rahmadani & Andrini (2021), namely the Mirror Image, the Current Image, the Wish Image, and the Multiple Image. This study uses quantitative methods with survey method approach, and using Lemeshow formula by taking the population of Instagram followers @scientiasquare.park has 133,000 followers as of February 21, 2024 by obtaining a sample of 97 respondents. The results showed that there is a positive and significant influence between the influence of Public Relations Marketing Strategy on the image with a high level of influence and significance.